Survey of Inmates in Local Jails, 2002 (United States) ([Verlag nicht ermittelbar], 2006)
This collection provides nationally representative data on persons held prior to trial and on convicted offenders serving sentences in local jails or awaiting transfer to state prisons. Data cover individual characteristics of jail inmates, current offenses, sentences and time served, criminal histories, jail activities, conditions and programs, prior drug and alcohol use and treatment, and health care services provided while in jail. Part 1, Numeric Data, contains numeric data for all questions in the survey, while Part 2, Alphanumeric Data, consists of non-numeric answers to the "Other, Specify" selection available for some of the questions.